How did I not see this coming? : a new manager's guide to avoiding total disaster - Tynan, Katy (ATD Press, 2018)
In How Did I Not See This Coming?, Tynan tells the fictional story of Julie, a onetime star producer, to illustrate how a new manager can successfully make the shift from a role without leadership responsibilities to one with them. Along the way, Tynan offers the five basic truths about management--starting with recognizing team values and strengths--truths that can be learned by anyone. You, too, can be the manager everyone's talking about--in a good way--because you're the one who figured it out.